Upregulated long noncoding RNA ENST00000470447.1 inhibits cell migration and invasion and predicts better disease‐free survival of oral cancer. Issue 9 (10th April 2019) - Chen, Fa; Yan, Lingjun; Wang, Jing; Lin, Lisong; Qiu, Yu; Hu, Zhijian; Wu, Junfeng; Bao, Xiaodan; Lin, Liangkun; Wang, Rui; Cai, Lin; Liu, Fengqiong; et al.
Abstract: Background: The aim of the present study was to assess the long noncoding RNA (lncRNA) expression profile of oral cancer and clarify the biological functions and clinical value of a novel lncRNA ENST00000470447.1. Method: Microarray assay was used to explore lncRNA expression profiles in three paired oral cancer and adjacent normal tissue samples. The expression of targeted lncRNA (ENST00000545372.1, ENST00000470447.1, and ENST00000412353.1) was validated by quantitative real‐time polymerase chain reaction. Then we evaluated the biological and clinical roles of ENST00000470447.1 in oral cancer by in vitro assays and multivariable Cox regression analysis. Results: LncRNAs were aberrantly expressed in oral cancer tissues. The expression levels of ENST00000470447.1 and ENST00000412353.1 in oral cancer tissues were significantly lower than those in matched adjacent noncancerous tissues ( P < .001). in vitro assays indicated that overexpression of ENST00000470447.1 significantly inhibited the proliferation, migration, and invasion ability of Tca‐8113 cells, whereas promoted the apoptosis of Tca‐8113 cells. Furthermore, ENST00000470447.1 expression was significantly correlated with tumor differentiation ( P = .030). Cox regression analyses demonstrated that high ENST00000470447.1 expression was associated with better disease‐free survival for patients with oral cancer (hazard ratio: 0.25, 95% CI: 0.06‐0.95; P = .041). Conclusion: Our findings suggest that ENST00000470447.1 can be served as a potential novel marker for recurrence and metastasis prediction of patients with oral cancer, which may provide a potential therapeutic target for oral cancer.